2022
DOI: 10.3390/ani12131697
|View full text |Cite
|
Sign up to set email alerts
|

Viral Co-Infections of Warthogs in Namibia with African Swine Fever Virus and Porcine Parvovirus 1

Abstract: Understanding virus circulation in wild animals, particularly those that have contact with domestic animals, is crucial for disease management and control. In Africa, warthogs are known to be asymptomatic carriers of porcine pathogens; a recent study in Namibia has shown them to be positive for Porcine circovirus-2 (PCV-2). In this study, the same samples used for the PCV-2 investigation in Namibia were further screened for the presence of African swine fever virus (ASFV) and porcine parvovirus 1 (PPV1) by PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The proportion of coinfections indicates that 25% of the pigs that tested positive for PPV3 were also positive for ASFV. These results corroborate with a previous study in South Kivu province, DRC [9] and China [16] where ASFV was found in pigs infected with PPV .This is further supported by reports of a survey on the Namibian warthog ecosystem showing a concurrent infection between ASFV and PPV type 1 (PPV1) [17]. High infection rates of ASFV and PPV3 were detected from Misisi and Goma territories, and this was mainly due to the increased displacement of pig breeders and their belongings from rural areas to towns as people ed heightened rebel insurgency in rural villages.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of coinfections indicates that 25% of the pigs that tested positive for PPV3 were also positive for ASFV. These results corroborate with a previous study in South Kivu province, DRC [9] and China [16] where ASFV was found in pigs infected with PPV .This is further supported by reports of a survey on the Namibian warthog ecosystem showing a concurrent infection between ASFV and PPV type 1 (PPV1) [17]. High infection rates of ASFV and PPV3 were detected from Misisi and Goma territories, and this was mainly due to the increased displacement of pig breeders and their belongings from rural areas to towns as people ed heightened rebel insurgency in rural villages.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 351 samples screened by PCR in this study, 31 (8.8%) were positive for PPV1 [i.e., Burkina Faso ( n = 2; positivity ratio = 3.85%), Ivory Coast ( n = 7; positivity ratio = 12.96%), Kenya ( n = 1; positivity ratio = 11.11%), Mozambique ( n = 17; positivity ratio = 17.71%), Senegal ( n = 2; positivity ratio = 11.76%), Tanzania ( n = 2; positivity ratio = 1.63%)]. Additionally, 40 sequences previously obtained from Namibia (positivity ratio = 36.35%) and Nigeria (positivity ratio = 20.6%) were included in the study [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…PPV1 nucleotide sequences spanning the same VP2 region obtained in the present study and originating from Europe, North and South America, and Asia were downloaded from GenBank (when the sampling country and date were available). In addition, sequences ( n = 40) from two African countries Namibia and Nigeria were included [ 14 , 15 , 16 ]. All the sequences were merged with the ones generated in the present study and aligned using MAFFT [ 17 ] and their quality was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Zimbabwe has reported relatively few outbreaks of ASF, with the earliest report being in 1961, caused by a genotype VIII ASFV [ 48 ]. In the early 90s, some outbreaks were investigated and related to genotype I and XVII [ 65 ], and more recently, in 2015, genotype II ASFV emerged in domestic pigs in Mashonaland Central Province in northern Zimbabwe [ 66 ].…”
Section: Geographical Distribution Of Ornithodoros ...mentioning
confidence: 99%
“…Initial typing efforts which confirmed genotype I in warthogs [ 47 ] and in domestic pig outbreaks in Windhoek in 1989 [ 65 ] appeared to support this. However, subsequent typing of the 2018 domestic pig outbreak strains viruses and those present in warthogs from the same region, 15 months after the outbreak, revealed that whilst genotype I viruses were present in both suid species, the strains detected in domestic pigs were distinct from those in wild suids [ 48 ].…”
Section: Geographical Distribution Of Ornithodoros ...mentioning
confidence: 99%